Pengaruh Terapi Pemberian Air Teh Hijau Terhadap Penurunan Skala Nyeri Menstruasi pada Mahasiswi Politeknik Negeri Subang - Gina Sri Utami; Novian Mahayu Adiutama; Wardah Fauziah (Calory Journal Medical Laboratory Journal, 2024)
Introduction: Women often complain of menstrual pain before or during menstruation, this pain often interferes with daily activities. An alternative to drinking green tea is considered to have the highest levels of polyphenols which can reduce pain. This study aimed prove the therapeutic effect of giving green tea water on reducing the scale of menstrual pain. Methods: The research was conducted on students of Program Studi Keperawatan Politeknik Negeri Subang with a quasi-experimental research design with a pre-post test design with control group. Sampling used a stratified random sampling with a total of 40 students. This research uses a research instrument in the form of a BPI (Brief Pain Inventory) questionnaire sheet. tested the independent t-test. Results: The results of this study showed that the mean menstrual pain scale in the intervention group before the green tea water therapy was 4.92 and the control group was 4.81, the average menstrual pain scale in the intervention group after the green tea water therapy was 1.25 and the control group was 3.56. Conclusions: Data analysis obtained a p value of 0.001 (< 0.05) which shows that there is a therapeutic effect of giving green tea water on reducing the scale of menstrual pain. Green tea water at a dose of 2.4 grams / 200 ml can reduce menstrual pain and is recommended for women who experience mild to moderate pain.